Analisis Pengaruh Efektivitas Program Jaminan Kesehatan Bali Mandara (JKBM) di Desa Pemecutan Kaja Kecamatan Denpasar Utara Kota Denpasar - Sutrisna, Wayan; Tisnawati, Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 9, September 2013 (pp. 401-433), 2013)
Poorness represent one of the internal issue life of society. Many governmental program which strived for the mengentaskan of poorness of society, but from some program which have been executed by government, in the reality still not yet earned to reach result of which is wanted, this matter seen from still to the number of impecunious resident which not yet can defray its health. This matter push government  1 January 2010 strarting Guarantee program Health Of Bali of Mandara (JKBM) which in destining to assist Bali society in service of free medication. Intention of this research is to know program effectiveness storey;level of JKBM and also to know the existence of change of earnings of impecunious household before and after becoming participant of JKBM. Determination of sampel at this research use formula of Slovin. Method data collecting weared by Method interview and kuisioner analyse used data at this research is deskriftif anlisis, effectiveness analysis and statistical test of nonparametrik. Characteristic participant of JKBM menunjukan that most participant of JKBM old age 47-55 year. Mean earnings of participant of JKBM before program executed by is Rp.660.273 later; then after program executed by mean earnings of participant of program mount to become Rp.810.958. Storey; Level Effectiveness aid program of JKBM [in] Countryside Acceleration of Kaja equal to 80%, meaning that aid of JKBM is very effective. Besides program the mentioned of JKBM can change earnings and also depress the expense of health of participant of this JKBM of menunjukan efficacy of program of JKBM in Countryside Pemecutan Kaja. Program of JKBM which have walked better have to is always evaluated by its execution.
Keywords: Effectiveness; Program of JKBM; Change of Earnings